Communication Strategies Used by Teacher - Darman Pangaribuan; Stefani Agustina; Anggie Pratiwi; Elfian Manalu; Yenita br Sembiring (Linguistic, English Education and Art (LEEA) Journal, 2020)
This thesis was aimed to find teacher communication strategies during classroom interaction. This research was conducted in SMP SWASTA Brigjend Katamso 1 Medan. The subject of this research was the English Teacher. We used a qualitative approach, more specifically classroom discourse analysis, in analyzing this study since the source of the data were communication strategies which are used by an English teacher in communicating with her students during an English teaching-learning activity. We took the data by recording 90 minutes of English Lessons. We used Faerch and Kasper as a framework for this data analysis, for the reason of its specification and newness. The result showed that the five strategies used were repetition. From those strategies, code-switching was the strategy that was most frequently used by the teacher during the process of teaching and learning. The teacher`s reasons for applying those communication strategies were to overcome the communication barriers that occur between the teacher and the students to help the students understand and memorize the material more accessible. The result of the interview also showed that the students had a good perception of the implementation of communication strategies used by the teacher in the classroom. Keywords: Achievement strategies, Communication strategies, Reduction strategies, Teacher